Novel molecular mechanisms and regeneration therapy for heart failure. (March 2016) - Oka, Toru; Morita, Hiroyuki; Komuro, Issei
Abstract: Heart failure (HF) is one of the leading causes of mortality in the world. Various molecular mechanisms have been proposed for HF, but its precise mechanisms are still largely unknown. In this review, summarizing the "President's Distinguished Lecture Award" of XX World Congress of International Society for Heart Research 2010 in Kyoto, Japan, we introduce recent our studies on HF, including 1) p53-induced suppression of Hif-1-induced angiogenesis as a novel mechanism of HF, 2) angiogenesis as a potential therapeutic strategy for HF, and 3) IGFBP-4 as a novel factor for cardiomyogenesis by inhibiting canonical Wnt signaling. Highlights: p53-induced suppression of Hif-1-induced angiogenesis as a novel mechanism of HF. Angiogenesis as a potential therapeutic strategy for HF IGFBP-4 as a novel factor for cardiomyogenesis by inhibiting canonical Wnt signaling